Hypoalbuminaemia is associated with mortality in patients undergoing cytoreductive nephrectomy. (15th December 2014) - Corcoran, Anthony T.; Kaffenberger, Samuel D.; Clark, Peter E.; Walton, John; Handorf, Elizabeth; Piotrowski, Zack; Tomaszewski, Jeffery J.; Ginzburg, Serge; Mehrazin, Reza; Plimack, Elizabeth; Chen, David Y.T.; Smaldone, Marc C.; et al.
<x xml:space="preserve">Abstract</x> Objective To evaluate whether poor nutrition is associated with mortality in patients undergoing cytoreductive nephrectomy (CN) for metastatic renal cell carcinoma (mRCC). Patients and Methods A multi‐institutional review of prospective databases identified 246 patients meeting inclusion criteria who underwent CN for mRCC from 1993 to 2012. Nutritional markers evaluated were: body mass index <18.5 kg/m2, serum albumin <3.5 g/dL, or preoperative weight loss of ≥5% of body weight. Primary outcomes were overall (OS) and disease‐specific survival (DSS). Secondary outcome was 'early mortality' defined as death at ≤6 months of surgery. Survival curves were estimated using the Kaplan–Meier product‐limit method and multivariate analysis using logistic regression was used to test associations between nutritional markers and survival outcomes. Results In all, 119 patients (median follow‐up 17 months) were categorised as having any abnormal nutrition parameter (48%). Hypoalbuminaemia was the only independent predictor of OS and DSS (OS: median 8 vs 23 months, P < 0.001; DSS: 11 vs 33 months, P < 0.001). On multivariate analysis, hypoalbuminaemia remained a significant predictor of death for both overall [hazard ratio (HR) 2, 95% confidence interval (CI) 1.4–2.8; P < 0.001) and disease‐specific mortality (HR 2.2, 95% CI 1.4–3.3; P < 0.001). Hypoalbuminaemia was also associated with early mortality (overall: P < 0.001 and disease specific: P = 0.002). Conclusion Patients with mRCC and hypoalbuminaemia undergoing CN have decreased OS and CSS, and increased risk of all‐cause and disease‐specific early mortality. As such, serum albumin may help risk stratify patients selected as candidates for CN. Furthermore, future work should evaluate whether nutritional depletion is a modifiable risk factor.